Peranan Orang Tua Dalam Mengembangkan Kreativitas Anak Usia Dini Di Masa Digital - Heri Hidayat; Mega Lestari; Ade Novi Siti Nurhayati; Gina Tsanaya (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2021)
This article is motivated by the importance of the role of parents in developing creativity in children in the currently developing digital era, the times in the global era which is marked by the rapid development of products and the use of information technology. The role of parents is very important to prepare the media optimally so that learning processes can run smoothly and can make children more active. The purpose of this research is to increase the competence of parents in developing the creativity of early childhood in this digital age so that it is more  optimal in its implementation. The method used in this study is a qualitative research method, which describes the urgency of the role of parents in developing early childhood creativity in this digital era. The results of this study indicate that the role of parents is very important in developing a child's creativity. Children's creativity can be determined in several factors, including heredity / heredity, where if the parents have certain talents, it is likely that their children will have the same talents.